Improving intoxicated witness recall with the Enhanced Cognitive Interview. - Crossland, Deborah; Kneller, Wendy; Wilcock, Rachel (Psychopharmacology, 2020)
Rationale: Witnesses and victims typically provide the central leads in police investigations, yet statistics from past research indicates in many instances these individuals are intoxicated. Objectives: To date, however, no research has looked at how best to interview such witnesses to maximise the amount of accurate information they recall. Methods: In the present research, whilst on a night out, participants watched a videoed theft whilst either sober or moderately (MBAC = 0.05%) or severely (MBAC = 0.14%) intoxicated. A week later, in a different location, participants were interviewed using either the Enhanced Cognitive (ECI) or Structured Interview. Results: The ECI was found to improve the recall accuracy and completeness of witness accounts across all three drinking conditions. However, no significant interaction was indicated between alcohol and interview condition. Conclusions: The study findings are discussed in terms of their real-world value in aiding police officers to elicit as complete and as accurate an account as possible from intoxicated witnesses.